Coronary heart disease in relation to age, sex, and the menopause. Issue 6111 (25th February 1978) - Heller, R F; Jacobs, H S
Abstract : Examination of the Registrar General's mortality data suggested that women do not lose protection from coronary heart disease (CHD) after the menopause. Apparently, at around the age of 50 men begin to lose a factor that had previously put them at increased risk of developing CHD compared with women. Male sex hormones may be risk factors for CHD, and further studies are needed to clarify their role in the aetiology of CHD in men.